Foot and Soccer Referees’: A Pilot Study Searching “Performance” Throughout Prevention - Gianturco, Luigi; Bodini, Bruno D.; Gianturco, Vincenzo; Pregliasco, Fabrizio E.; Cascio, Marta; Serafin, Antonio; Turiel, Maurizio (Frontiers in Physiology, 2018)
Soccer refereeing is a “not-conventional” sport in which aerobic workload is prevalent. Along the years, several studies have attempted to define best markers of referees’ performance. Many studies focused their attention on field tests and their relationship with aerobic power. Instead, in this study, starting by a medical assessment satisfying the FIFA 11+ criteria for injuries prevention, we have investigated the foot of soccer referees and we have also wanted to find possible and/or unespected improvements in performance. As performance marker we have used the referral field test for soccer referees that is internationally validated and known as Yo-Yo test (YYiR1). Whilst standardized foot posture index (FPI) questionnaire was used for screening foot referees conditions (40 young, all men by sex, with mean age 23.47±4.36). Analyzing collected data we have demonstrated by means of Read-Cressie Chi square test that neutral FPI is an important favour item affecting YYiR1 results. Futher studies will be necessary in order to confirm this our pilot investigation.